WOMAN'S MYTH INFLUENCE IN TOURISM OBJECTS NAME IN PULAU BANGKA: AN ECOFEMINISM STUDY - Fitri, Dian; Wulansari, Dini; Ferianda, Sandy (BASIS (Bahasa dan Sastra Inggris), 2022)
Since there were many stories told by the society related to the name of the tourism places, the researchers were interested to find out the story behind the name of the tourism places in Belinyu, Central Bangka called, Pulau Putri. This research mainly focused on finding what kind of myth existed in Pulau Putri and discovered how the myth protected the environment. The study employed two major theories namely Myth by Levi Strauss and ecofeminism by Jamie Thompson to shape the understanding of this research. The methodology employed in this research was the qualitative method. From the data collected through interviews with locals, the results showed that there was a myth told by the ancestors living around the area about a woman spirit. Furthermore, the existence of the spirit hence became the protection for preserving nature and also the environment. Moreover, not only did myth name the tourism places, but it also helped or became the symbol of protection of the environment.